2017
DOI: 10.1021/acsomega.7b00538
|View full text |Cite
|
Sign up to set email alerts
|

NiOx Hole Transport Layer for Perovskite Solar Cells with Improved Stability and Reproducibility

Abstract: In this study, highly stable, low-temperature-processed planar lead halide perovskite (MAPbI 3– x Cl x ) solar cells with NiO x interfaces have been developed. Our solar cells maintain over 85% of the initial efficiency for more than 670 h, at the maximum power point tracking (MPPT) under 1 sun illumination (no UV-light filtering) at 30 °C, and over 73% of the initial efficiency for more than 1000 h, at the acceleratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
201
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(217 citation statements)
references
References 45 publications
9
201
0
Order By: Relevance
“…[46][47][48]50] As shown in Figure 1, this problem is avoided in this work by using oxygen as process gas. [46][47][48]50] As shown in Figure 1, this problem is avoided in this work by using oxygen as process gas.…”
Section: Fundamental Characteristics Of Electron Beam Evaporated Nickmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48]50] As shown in Figure 1, this problem is avoided in this work by using oxygen as process gas. [46][47][48]50] As shown in Figure 1, this problem is avoided in this work by using oxygen as process gas.…”
Section: Fundamental Characteristics Of Electron Beam Evaporated Nickmentioning
confidence: 99%
“…In a tandem solar cell, the strong parasitic absorption in spiro-MeOTAD used in the top solar cell can cause significant current losses, thus motivating the search for alternative materials to achieve the highest possible PCEs. [45][46][47][48][49] The most striking benefit of sputtering is the ease of additional doping (e.g., with Co, Cu, or Mg) to improve the conductivity of the NiO x layer. Inorganic HTL materials are among the most promising materials on the route toward highly stable and inexpensive perovskite solar cells for single-junction as well as multi-junction devices.…”
mentioning
confidence: 99%
“…However, due to its acidic nature and hygroscopic character, devices with PEDOT:PSS layers might degrade faster than devices with e.g. NiO x hole transport layers, which have a similar valence band energy as PEDOT:PSS films [10][11][12][13][14]. Some research groups also reported better crystallinity of the perovskite film on a NiO x layer than on PEDOT:PSS [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…We find the time constant of the hole injection and the quantity of the injected holes depend crucially on the choice of the HTM, and discuss the observed hole injection dynamics in comparison with the device performance of the solar cells containing the same interfaces. Samples for spectroscopic measurements consist of a glass substrate, a thin layer of HTM prepared by either spin-coating (PTAA and PEDOT:PSS) or sputtering (NiO x ) [15,16], and a 250-nm thick crystalline MAPbI 3 film [17,18], as schematically shown in Fig. 1b.…”
mentioning
confidence: 99%